Deficiencies in the Mitochondrial Electron Transport Chain Affect Redox Poise and Resistance Toward Colletotrichum higginsianum - McCollum, Christopher; Geißelsöder, Sonja; Engelsdorf, Timo; Voitsik, Anna Maria; Voll, Lars M. (Frontiers in Plant Science, 2019)
To investigate how the integrity of the mitochondrial electron transport chain (mETC) influences susceptibility of Arabidopsis towards C. higginsianum, we have selected previously characterized mutants with defects at different stages of the mETC, namely the complex I mutant ndufs4, the complex II mutant sdh2-1, the complex III mutant ucr8-1 and a mutant of the uncoupling protein, ucp1-2. Relative to wild type, the selected complex I, II and III mutants showed decreased total respiration, increased alternative respiration as well as increased redox charge of the NADP(H) pool and decreased redox charge of the NAD(H) pool in the dark. In the light, mETC mutants accumulated free amino acids, albeit to varying degrees. Predominantly glycine and serine, which are involved in carbon recycling from photorespiration, and N-rich amino acids were increased in mETC mutants compared to the wild type. Taking together the physiological phenotypes of all examined mutants, our results suggest a connection between the limitation in the re-oxidation of reducing equivalents in the mitochondrial matrix and the induction of nitrate assimilation into free amino acids in the cytosol, which seems to be engaged as an additional sink for reducing power. The sdh2-1 mutant was less susceptible to C. higginsianum and did not show hampered salicylic acid (SA) accumulation as previously reported for SDH1 knockdown plants. Succinate accumulation was less pronounced in sdh2-1 compared to mutants defective in SDH1 activity. The ROS burst remained unaffected in sdh2-1, demonstrating that subunit SDH2 is not involved in the control of ROS production and SA signaling by complex II. The ndufs4 mutant showed only 20% of C. higginsianum colonization compared to wild type. The ROS burst and the production of callose papillae was significantly increased in ndufs4, indicating that the restriction of respiratory metabolism positively affects pre-penetration resistance of Arabidopsis. Taking metabolite profiling data from all investigated mETC mutants, a strong positive correlation of NADPH pool size, pyruvate contents and other metabolites associated with redox poise and energy charge with resistance towards C. higginsianum was evident, indicating that limitations in the mETC can also support resistance at post-penetration stages by improving the availability of metabolic power.